1998
DOI: 10.1038/sj.bmt.1701505
|View full text |Cite
|
Sign up to set email alerts
|

Mobilisation of healthy donors with lenograstim and transplantation of HLA-genoidentical blood progenitors in 54 patients with hematological malignancies: a pilot study

Abstract: Summary:Blood cell transplantation (BCT) is now common practice in the autologous setting. We performed a pilot study of allogeneic BCT, collected after the priming of an HLA-identical sibling with a glycosylated rhu-G-CSF (lenograstim) (10 g/kg). genitors allows easy harvest with cytapheresis, and collection of a better quality graft than after traditional BM harvest.2 In the autologous setting, this effectively leads to faster neutropenic reconstitution but also to accelerated platelet reconstitution. This q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…41,42 Moreover, a minimal CD34+ cell dose was shown necessary for engraftment in autologous PBSC transplantation. 43 In the current study, as has been suggested by our previous work, 23 an increased allogeneic CD34+ cell dose leads to a faster neutrophil and platelet engraftment. This observation is supported by other studies.…”
Section: Cd34+ Cell Dose and Chronic Gvhd M Mohty Et Alsupporting
confidence: 65%
See 1 more Smart Citation
“…41,42 Moreover, a minimal CD34+ cell dose was shown necessary for engraftment in autologous PBSC transplantation. 43 In the current study, as has been suggested by our previous work, 23 an increased allogeneic CD34+ cell dose leads to a faster neutrophil and platelet engraftment. This observation is supported by other studies.…”
Section: Cd34+ Cell Dose and Chronic Gvhd M Mohty Et Alsupporting
confidence: 65%
“…These patients were included in two consecutive trials by the SFGM-TC teams and were previously reported for other purposes. 11,23 The majority of the patients included in this analysis (n ¼ 59) were treated at the Marseille, Montpellier, and Lyon transplantation centers. Written informed consent was obtained from each patient and donor.…”
Section: Patients and Donorsmentioning
confidence: 99%
“…steroids. Other studies have revealed a slightly shorter hospital stay, 13,36 but readmission seems to be more frequent among the PBPC recipients. A short hospital stay is important for the patients and their families, and could also have economic implications, an issue, which is not estimated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the BM group, not surprisingly, the maximum pain experienced by donors followed the surgery itself when donors recover from general anesthaesia. Although a lot of clinical studies had already reported on the toxicity of G-CSF for healthy donors, [13][14][15][16] none had evaluated the impact of G-CSF stimulation on subjective well-being. Our study confirms that G-CSF stimulation is the most painful part of the harvesting procedure for BC donors and cytapheresis generated only moderate pain.…”
Section: Discussionmentioning
confidence: 99%